ANALYSIS OF PRESUPPOSITION IN THE MOVIE FIVE FEET APART BY JUSTIN BALDONI - Manurung, Neysa Meviola; Silalahi, Charles David Marudut (Cahaya Ilmu Bangsa Institute, 2025)
This study examines the use of presupposition in the movie Five Feet Apart directed by Justin Baldoni, focusing on its role in enhancing the narrative and character interactions. Presupposition, a linguistic concept that assumes certain information to be true within communication, is analyzed to explore how it contributes to the film’s emotional depth, thematic development, and overall storytelling. The research applies a qualitative approach to identify and categorize the types of presuppositions present, such as existential, lexical, factive, non-factive, structural, and counterfactual. It further investigates how these presuppositions function in the dialogues to convey implicit meanings, reveal character motivations, and foster relational dynamics among the protagonists. The findings highlight that presuppositions are strategically employed to subtly portray themes such as love, illness, resilience, and the boundaries imposed by cystic fibrosis, which the central characters face. By embedding unspoken truths and shared understandings within the conversations, the film effectively engages viewers, making the narrative more relatable and emotionally impactful. This study contributes to the fields of pragmatics and film studies by demonstrating how presupposition can be a powerful tool in cinematic storytelling, enriching both the linguistic and emotional layers of a narrative. It underscores the importance of linguistic analysis in understanding the deeper elements of film communication and the nuanced ways in which language shapes audience perceptions and experiences.